Mineralization and efficiency index of nitrogen in cattle manure fertilizers on the soil - Eckhardt,Daniel Pazzini (2016)
ABSTRACT: This research aimed to evaluate the mineralization of nitrogen (N) and to define the efficiency index (EI) of N after the addition of organic fertilizers based on cattle manure on the soil under laboratory conditions. A completely randomized statistical design with four replicates was used. The treatments were set as follows: T1) Soil (control); T2) Soil + vermicompost of cattle manure (CMV); T3) Soil + cattle manure and straw compost (CMS); and T4) Soil + cattle manure (CM). Experimental units were constituted by acrylic flasks with 5 x 5cm (height x diameter). Each flask was added with 135g of wet soil and 2.20, 2.45 and 2.27g of CMV, CMS and CM, respectively. Treatments were incubated at 25°C and the amount of mineral N from the soil (N-NH4+ and N-NO2- + N-NO3-) was determined at the beginning of the experiment and after 7, 14, 28, 56 and 112 days of incubation. The highest concentration of N-NO2- + N-NO3- in the soil were observed within the CMS treatment. The EI of N was of 27, 23 and 22% for CMS, CMV and CM, respectively. The mineralization of N from organic fertilizers based on cattle manure occurs on its vast majority within the first 28 days after its addition to the soil. The EI of N from the organic fertilizers based of cattle manure was higher for CMS>CMV>CM and achieved only 80% of what expected for organic fertilizers derived from cattle manure.